Preparation method of composite metal oxide nano powder
By using a specific ratio of precursor salt and metal source salt in the molten salt medium, combining hydroxide and urea, and performing efficient reaction and dispersion treatment, the problem of complex and high-temperature calcination of the existing composite metal oxide nanopowder preparation methods is solved, and the rapid and low-cost preparation of composite metal oxide nanopowders and the controllability of the morphological dimensions is achieved.
Patent Information
- Application Number
- CN202510101150.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-22
AI Technical Summary
The existing preparation methods for composite metal oxide nanopowders are complex and require multiple steps. High-temperature calcination leads to high production costs, high energy consumption and safety hazards, making it difficult to achieve industrialization.
Using a molten salt medium, a precursor salt, a metal source salt, sodium hydroxide or potassium hydroxide and urea are mixed at a certain mass ratio to conduct a sufficient reaction, and then heat it up to the reaction temperature in an inert gas atmosphere, control the reaction temperature and time, and finally disperse and dry it ultrasonically to obtain a composite metal oxide nanopowder.
It realizes the rapid and efficient preparation of composite metal oxide nano powder, controllable material morphology and size, low cost, low energy consumption, suitable for large-scale production, simplify the process flow and reduce the difficulty of industrialization.
Smart Images

Figure CN119911959A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of powder material preparation, and in particular relates to a method for preparing composite metal oxide nano powder. Background Art
[0002] Composite metal oxides have multiple metal atoms and therefore have variable valence states, and have advantages such as good stability and strong redox activity. They have great application prospects in energy storage, catalytic degradation, water separation, sensors and other fields. The nanoscale material structure size enables functional materials to often exhibit different or better performance than large-size bulk materials. Therefore, the nanostructured materials of composite metal oxides can exhibit excellent functional activity and nanosize effects, and have broad research potential. At the same time, in specific usage scenarios, nanopowder materials are often better adapted to actual application scenarios, and the strength of performance can be roughly controlled by controlling the amount, which can greatly improve production convenience and promote industrial development.
[0003] At present, the preparation methods of composite metal oxide nanopowders mainly include wet chemical method accompanied by high temperature calcination, ball milling method, electrospinning accompanied by high temperature calcination method, etc. These methods need to be carried out in multiple steps, and the instruments and equipment used are diverse and complex. Some need to customize special functions, and it is difficult to control the preparation process. On the other hand, the above methods usually require high temperature calcination above 800°C, which not only increases time and production costs, but also has certain safety hazards in the operation process. Some methods are too complicated, greatly increase production costs, and cannot be industrialized. Therefore, the preparation technology of composite metal oxide nanopowders that adapt to the market and industrial production has always been technically difficult, and better preparation methods are rarely reported.
[0004] For example, patent CN202410544891.0 discloses a method for preparing a composite metal oxide catalyst and its application in the synthesis of antioxidant 245. The invention uses zinc nitrate as a zinc source, aluminum nitrate as an aluminum source, potassium hydroxide as a potassium source, and sodium hydroxide as a sodium source, and first performs hydrothermal synthesis and then undergoes a high-temperature calcination process to prepare a composite metal oxide catalyst with a high specific surface area. Using a variety of raw materials is expensive; the synthesis process needs to be carried out in multiple steps, and the process is complicated, which is not conducive to industrialization. Usually, such wet chemical methods are combined with high-temperature calcination processes, such as patent CN202310457753.4, which provides a method for preparing a core-shell structured cerium-manganese bimetallic oxide with the participation of an interfacial reaction, CN202410944104.1, which provides an iron silicon magnetic powder core coated with a bimetallic oxide in situ and a preparation method thereof, and CN202311679060.6, which provides a multi-metal oxide nanosheet and a preparation method thereof, etc., all require at least three steps or more of the process, and the production cycle is long, the controllability is poor, and the cost is high. For example, patent CN201811543888.8 discloses a preparation method of a metal oxide or its composite material, a metal oxide or its composite material and its application, and a battery. The preparation method disclosed in the patent requires first dissolving the substrate in an organic salt medium to obtain a solid solution, then separating the solid solution into an insoluble product, and calcining at 500-800°C to obtain a metal oxide or its composite material. The synthesis process is difficult to control and is carried out in multiple steps, which has high requirements for industrialization. For example, patent CN201711489742.5 provides a preparation method for a manganese-chromium binary metal oxide energy storage material, and the product is a powder. The method uses a coprecipitation method to mix the raw materials, after 0.5-2 days of aging, and then calcining at high temperature under a specific atmosphere, and finally grinding and screening to finally obtain the product. Similar chemical precipitation methods are currently one of the most commonly used methods for industrial production of metal oxides, but it is not difficult to see that such a production process has cumbersome steps, produces a large amount of waste liquid, requires high temperature, and the coprecipitation conditions are difficult to control, which seriously pollutes the environment and is costly.
[0005] Compared with the above preparation technology, the high polarity and high viscosity of molten salt make the reactants therein have a shorter diffusion distance, so that nanoscale powders can be quickly synthesized. For example, patent CN201611186961.1 discloses a method for preparing ion intercalation type two-dimensional materials, which adopts the molten salt method to make the salt molten at a predetermined temperature, and add the metal salt precursor to the molten salt, take it out after the reaction for a predetermined time, cool it, wash it, filter it and dry it, and then obtain the ion intercalation type two-dimensional material; cation intercalation type metal oxides and anion intercalation type metal hydroxides can be obtained. However, it is difficult to prepare binary metal oxides and composite metal oxides by this method. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a composite metal oxide nanopowder, and the morphology and size of the nanostructure prepared by the method of the present invention are controllable, and the method has strong versatility, low cost, low energy consumption and excellent performance. The present invention provides a method for preparing a composite metal oxide nanopowder, comprising the following steps:
[0007] (1) fully mixing a precursor salt, salts of two different metal sources, sodium hydroxide or potassium hydroxide, and urea in a certain mass ratio to form a mixed reactant;
[0008] The sodium hydroxide or potassium hydroxide is used as a dispersant, and the degree of mutual adhesion between the nanoparticles of the composite metal oxide nanopowder material in step (6) is regulated by adjusting the amount of the dispersant:
[0009] By increasing the amount of sodium hydroxide or potassium hydroxide, the degree of adhesion between nanoparticles is reduced, and powder with a smaller particle size is obtained;
[0010] By reducing the amount of sodium hydroxide or potassium hydroxide, the degree of adhesion between nanoparticles is reduced, and a powder with a larger particle size is obtained;
[0011] (2) In an inert gas atmosphere, the mixed reactants of step (1) are heated from room temperature to a reaction temperature at a certain heating rate, kept heated to a molten state, and reacted for a period of time;
[0012] (3) cooling the reaction system of step (2) to a certain temperature along with the furnace, and keeping the temperature for a period of time;
[0013] (4) heating the reaction system of step (3) to a secondary reaction temperature at a certain heating rate and reacting for a period of time;
[0014] (5) Cooling the product of step (4) to room temperature in the furnace, dispersing it in deionized water by ultrasonic, and washing it by centrifugation with deionized water; improving the crystallinity of the product by step (3), and improving the dispersibility of the product by steps (4) and (5), so that the product has better crystallinity and the nanoparticles are uniform and dispersed.
[0015] (6) Completely drying the washed product to obtain a composite metal oxide nanopowder material.
[0016] Preferably, the precursor salt refers to a salt with a melting point below 500° C., including any one or more of the following mixtures: nitrates, chlorides, sulfates, phosphates, acetates, and carbonates.
[0017] The crystallinity of the product is improved through step (3), and the dispersibility of the product is improved through steps (4) and (5), so that the crystallinity of the product is better and the nanoparticles are uniform and dispersed.
[0018] Preferably, the salts of the two different metal sources include nitrates, sulfates, chlorides, phosphates, titanates, tungstates, acetates, molybdates or carbonates of any two of the metal elements copper, manganese, nickel, cobalt, zinc, iron, titanium, aluminum, tin, vanadium, chromium, molybdenum, ruthenium, tungsten, zirconium, lanthanum and cerium; wherein the mass ratio of the salts of the two different metal sources is in the range of 10 to 0.1:1, and the specific amount is configured according to the phase composition of the composite metal oxide to be obtained.
[0019] Preferably, the mass ratio of the precursor salt, the salt of two different metal sources, sodium hydroxide or potassium hydroxide, and urea is (100-1): (50-0.5): (5-1): 1. Among them, sodium hydroxide or potassium hydroxide is used as a dispersant in the reaction system. The degree of mutual adhesion between the nanoparticles of the final product can be regulated by adjusting the amount of the dispersant. Too little dispersant will cause serious adhesion between the product particles, so that the product forms a block on a macro scale, which is seriously hardened. Too much dispersant will waste raw materials. Urea is used as a fluxing agent and precipitant in the reaction system. By adjusting its amount, the reaction melting speed of the reaction system and the crystallinity of the final product can be regulated. Too little urea will reduce the reaction melting speed and the product tends to be amorphous and non-crystalline. Too much urea will lead to insufficient reaction and loss of raw materials.
[0020] Preferably, the heating rate in step (4) is in the range of 0.5 to 10° C. / min, the reaction temperature is in the range of the melting point to the decomposition temperature of the precursor salt, and the reaction time is in the range of 60 seconds to 6 hours.
[0021] Preferably, the heating rate in step (2) is in the range of 0.5 to 10° C. / min, the reaction temperature is in the range of the melting point to the decomposition temperature or boiling point of the precursor salt, and the reaction time is in the range of 60 seconds to 6 hours.
[0022] Preferably, the temperature range of cooling to a certain temperature in step (3) is 50 to 150° C., and the range of the insulation time is 0.5 to 5 hours.
[0023] Preferably, the size and morphology of the nanoparticles of the composite metal oxide nanopowder material in step (6) are adjusted by adjusting the heating rates in step (2) and step (4):
[0024] By increasing the heating rate, the size of the nanoparticles increases and the nanoparticles form a polyhedral structure; by decreasing the heating rate, the size of the nanoparticles decreases and the nanoparticles form a spherical structure;
[0025] Preferably, the degree of crystallization of the composite metal oxide nanopowder material is regulated by regulating the reaction temperature in step (2) and the certain temperature in step (3):
[0026] By increasing the temperature difference between the reaction temperature in step (2) and the certain temperature in step (3), the degree of crystallization is increased, and by reducing the temperature difference between the reaction temperature in step (2) and the certain temperature in step (3), the degree of crystallization is reduced. The faster the heating rate in step (2) and step (4), the faster the ion movement rate in the molten reactant, and the huge heat energy in a short time intensifies the ion agglomeration. The obtained product is usually a polyhedral structure, and the size of the nanoparticles is relatively large; on the contrary, the product nanoparticles tend to be spherical structures, and the size diameter is relatively smaller.
[0027] The main advantages of the present invention are as follows:
[0028] (1) The present invention realizes rapid and efficient preparation of a variety of composite metal oxide nanopowder materials, and is easy to mass produce;
[0029] (2) By regulating the ratio of the mixed reactants and the reaction temperature, time, and heating rate parameters, the phase, morphology, and size of the composite metal oxide product can be regulated.
[0030] (3) The present invention utilizes the high viscosity and polarity of the molten salt to achieve rapid matching of the nucleation and growth of ions and oxides, so that the reaction can efficiently synthesize uniform and pure composite metal oxide nanomaterials;
[0031] (4) Compared with wet chemical synthesis, the synthesis method of the present invention has a smaller Stokes radius than hydrated ions in the molten salt medium, a lower reaction barrier, and a faster reaction rate, which reduces energy consumption, saves time costs, and reduces the difficulty of industrialization.
[0032] (5) The preparation method of the present invention is simple, environmentally friendly, low-cost, and the morphology and size of the nanopowders are controllable. The prepared nanopowders are expected to be widely used in energy and environmental fields such as energy storage, catalysis, and sensing. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the specific implementation of the present invention or the technical solutions in the prior art, the following will briefly introduce the drawings required for the specific implementation or the prior art description. Some specific embodiments of the present invention will be described in detail in an exemplary but not restrictive manner with reference to the drawings. The same reference numerals in the drawings indicate the same or similar components or parts. Those skilled in the art should understand that these drawings are not necessarily drawn to scale. In the drawings:
[0034] Figure 1 This is a field emission scanning electron microscope photograph of the copper-tin composite oxide prepared in Example 1.
[0035] Figure 2 This is a field emission scanning electron microscope photograph of the zinc-cerium composite oxide prepared in Example 2.
[0036] Figure 3 This is a field emission scanning electron microscope photograph of the manganese-titanium composite oxide prepared in Example 3.
[0037] Figure 4 This is a field emission scanning electron microscope photograph of the iron-nickel composite oxide prepared in Example 4.
[0038] Figure 5 The X-ray diffraction patterns of the composite metal oxide nanopowders prepared in Examples 5 to 10 are as follows: a is the copper-iron composite oxide prepared in Example 5, b is the nickel-iron composite oxide prepared in Example 6, c is the cobalt-copper composite oxide prepared in Example 7, d is the iron-manganese composite oxide prepared in Example 8, e is the zinc-copper composite oxide prepared in Example 9, and f is the zinc-nickel composite oxide prepared in Example 10.
[0039] Figure 6 X-ray diffraction patterns of the nickel-cobalt composite oxide nanopowders prepared in Examples 11 to 14, specifically: g is prepared in Example 11, h is prepared in Example 12, i is prepared in Example 13, and j is prepared in Example 14. DETAILED DESCRIPTION
[0040] The present invention is further described below in conjunction with examples, but the present invention is not limited to the following examples.
[0041] Example 1
[0042] (1) 10g sodium nitrate, 2g tin tetrachloride, 1g copper chloride, 0.9g sodium hydroxide and 2.1g urea are fully mixed to form a mixed reactant; (2) In an argon atmosphere, the temperature is increased from room temperature to 600°C at a heating rate of 5°C / min, and the reaction is kept at this temperature for 1 hour; (3) The mixture is cooled to 100°C in the furnace and kept at this temperature for 2 hours; (4) The mixture is heated to 350°C at a heating rate of 5°C / min and the reaction is carried out for 1 hour; (5) The product of step (4) is cooled to room temperature in the furnace, ultrasonically dispersed in deionized water, and washed by centrifugation with deionized water; (6) The washed product is completely dried to obtain a copper-tin composite oxide nanopowder material. The field emission scanning electron microscope photograph of the obtained nanopowder material is shown in the figure. Figure 1 As shown, the surface morphology observation results show that the diameter of the nanopowder particles is about 10nm, the nanoparticles are interconnected to form a stacked layer structure, the interval between layers is about 1nm, and there are abundant pores.
[0043] Example 2
[0044] (1) 10 g of sodium nitrate, 5 g of sodium chloride, 2 g of zinc chloride, 0.5 g of cerium nitrate, 0.9 g of sodium hydroxide, and 2.1 g of urea are fully mixed to form a mixed reactant; (2) In an argon atmosphere, the temperature is increased from room temperature to 550°C at a heating rate of 2°C / min, and the reaction is kept at this temperature for 2 hours; (3) The temperature is cooled to 100°C in the furnace and kept at this temperature for 1 hour; (4) The temperature is increased to 300°C at a heating rate of 2°C / min and the reaction is carried out for 1 hour; (5) The product of step (4) is cooled to room temperature in the furnace, ultrasonically dispersed in deionized water, and washed by centrifugation with deionized water; (6) The washed product is completely dried to obtain a zinc-cerium composite oxide nanopowder material. The field emission scanning electron microscope photograph of the obtained nanopowder material is shown in the figure. Figure 2 As shown, the surface morphology observation results show that the diameter of the nanopowder particles is about 3 to 5 nm, and the tiny nanoparticles are tightly connected to form a fine mesh pore structure.
[0045] Example 3
[0046] (1) 20g potassium nitrate, 5g potassium chloride, 4g manganese nitrate, 4g titanyl sulfate, 1.2g sodium hydroxide and 3g urea are fully mixed to form a mixed reactant; (2) In an argon atmosphere, the temperature is increased from room temperature to 600°C at a heating rate of 5°C / min, and the reaction is kept at this temperature for 2.5 hours; (3) The temperature is cooled to 50°C in the furnace and kept at this temperature for 1 hour; (4) The temperature is increased to 400°C at a heating rate of 5°C / min and the reaction is carried out for 1 hour; (5) The product of step (4) is cooled to room temperature in the furnace, ultrasonically dispersed in deionized water, and washed by centrifugation with deionized water; (6) The washed product is completely dried to obtain a manganese-titanium composite oxide nanopowder material. The field emission scanning electron microscope photograph of the obtained nanopowder material is shown in the figure. Figure 3 As shown, the surface morphology observation results show that the nanoparticles are interconnected to form a network structure with rich pores, and the diameter of the nanopowder particles is about 5nm.
[0047] Example 4
[0048] (1) 50g potassium nitrate, 5g ferric chloride, 5g nickel nitrate, 2.7g sodium hydroxide and 6.3g urea are fully mixed to form a mixed reactant; (2) In an argon atmosphere, the temperature is increased from room temperature to 500°C at a heating rate of 0.5°C / min, and the reaction is kept at this temperature for 6 hours; (3) The temperature is cooled to 100°C in the furnace and kept at this temperature for 2 hours; (4) The temperature is increased to 350°C at a heating rate of 0.5°C / min and the reaction is carried out for 2 hours; (5) The product of step (4) is cooled to room temperature in the furnace, ultrasonically dispersed in deionized water, and washed by centrifugation with deionized water; (6) The washed product is completely dried to obtain an iron-nickel composite oxide nanopowder material. The field emission scanning electron microscope photograph of the obtained nanopowder material is shown in the figure. Figure 4As shown, the surface morphology observation results show that the diameter of the nanopowder particles is about 7nm, and the nanoparticles are interconnected to form a porous structure.
[0049] Example 5
[0050] (1) 10 g of sodium nitrate, 5 g of sodium chloride, 2 g of copper nitrate, 2 g of iron nitrate, 0.9 g of sodium hydroxide and 2.1 g of urea are fully mixed to form a mixed reactant; (2) In an argon atmosphere, the temperature is increased from room temperature to 650°C at a heating rate of 5°C / min, and the reaction is kept at this temperature for 2 hours; (3) The temperature is cooled to 50°C in the furnace and kept at this temperature for 1 hour; (4) The temperature is increased to 500°C at a heating rate of 2°C / min and the reaction is carried out for 1 hour; (5) The product of step (4) is cooled to room temperature in the furnace, ultrasonically dispersed in deionized water, and washed by centrifugation with deionized water; (6) The washed product is completely dried to obtain a copper-iron composite oxide nanopowder material. The X-ray diffraction spectrum of the obtained nanopowder is as follows: Figure 5 As shown in curve a, the results show that the oxide is a copper-iron composite oxide.
[0051] Example 6
[0052] (1) 10 g of sodium nitrate, 5 g of sodium chloride, 2 g of ferric nitrate, 2 g of nickel nitrate, 0.9 g of sodium hydroxide and 2.1 g of urea are fully mixed to form a mixed reactant; (2) In an argon atmosphere, the temperature is increased from room temperature to 650°C at a heating rate of 5°C / min, and the reaction is kept at this temperature for 6 hours; (3) The temperature is cooled to 50°C in the furnace and kept at this temperature for 2 hours; (4) The temperature is increased to 500°C at a heating rate of 5°C / min and the reaction is carried out for 6 hours; (5) The product of step (4) is cooled to room temperature in the furnace, ultrasonically dispersed in deionized water, and washed by centrifugation with deionized water; (6) The washed product is completely dried to obtain a nickel-iron composite oxide nanopowder material. The X-ray diffraction spectrum of the obtained nanopowder is as follows: Figure 5 As shown in curve b, the results show that the oxide is a nickel-iron composite oxide.
[0053] Example 7
[0054] (1) 10 g of sodium nitrate, 5 g of sodium chloride, 2 g of cobalt nitrate, 2 g of copper nitrate, 0.9 g of sodium hydroxide and 2.1 g of urea are fully mixed to form a mixed reactant; (2) In an argon atmosphere, the temperature is increased from room temperature to 500°C at a heating rate of 5°C / min, and the reaction is kept at this temperature for 6 hours; (3) The temperature is cooled to 150°C in the furnace and kept at this temperature for 1 hour; (4) The temperature is increased to 300°C at a heating rate of 5°C / min and the reaction is carried out for 6 hours; (5) The product of step (4) is cooled to room temperature in the furnace, ultrasonically dispersed in deionized water, and washed by centrifugation with deionized water; (6) The washed product is completely dried to obtain a cobalt-copper composite oxide nanopowder material. The X-ray diffraction spectrum of the obtained nanopowder is as follows: Figure 5As shown in curve c, the results show that the oxide is a cobalt-copper composite oxide.
[0055] Example 8
[0056] (1) 10 g of sodium nitrate, 5 g of sodium chloride, 2 g of ferric nitrate, 2 g of manganese nitrate, 0.9 g of sodium hydroxide and 2.1 g of urea are fully mixed to form a mixed reactant; (2) In an argon atmosphere, the temperature is increased from room temperature to 650°C at a heating rate of 5°C / min, and the reaction is kept at this temperature for 2 hours; (3) The temperature is cooled to 100°C in the furnace and kept at this temperature for 2 hours; (4) The temperature is increased to 300°C at a heating rate of 10°C / min and the reaction is carried out for 4 hours; (5) The product of step (4) is cooled to room temperature in the furnace, ultrasonically dispersed in deionized water, and washed by centrifugation with deionized water; (6) The washed product is completely dried to obtain an iron-manganese composite oxide nanopowder material. The X-ray diffraction spectrum of the obtained nanopowder is as follows: Figure 5 As shown in curve d, the results show that the oxide is an iron-manganese composite oxide.
[0057] Example 9
[0058] (1) 10 g of sodium nitrate, 5 g of sodium chloride, 2 g of zinc nitrate, 2 g of copper sulfate, 0.9 g of sodium hydroxide and 2.1 g of urea are fully mixed to form a mixed reactant; (2) In an argon atmosphere, the temperature is increased from room temperature to 530°C at a heating rate of 2°C / min, and the reaction is kept at this temperature for 4 hours; (3) The temperature is cooled to 90°C in the furnace and kept at this temperature for 5 hours; (4) The temperature is increased to 300°C at a heating rate of 2°C / min and the reaction is carried out for 4 hours; (5) The product of step (4) is cooled to room temperature in the furnace, ultrasonically dispersed in deionized water, and washed by centrifugation with deionized water; (6) The washed product is completely dried to obtain a zinc-copper composite oxide nanopowder material. The X-ray diffraction spectrum of the obtained nanopowder is as follows: Figure 5 As shown in curve e, the results show that the oxide is a zinc-copper composite oxide.
[0059] Example 10
[0060] (1) 10 g of sodium nitrate, 5 g of sodium chloride, 2 g of zinc nitrate, 2 g of nickel nitrate, 0.9 g of sodium hydroxide and 2.1 g of urea are fully mixed to form a mixed reactant; (2) In an argon atmosphere, the temperature is increased from room temperature to 480°C at a heating rate of 5°C / min, and the reaction is kept at this temperature for 2 hours; (3) The temperature is cooled to 80°C in the furnace and kept at this temperature for 1 hour; (4) The temperature is increased to 200°C at a heating rate of 5°C / min and the reaction is carried out for 1 hour; (5) The product of step (4) is cooled to room temperature in the furnace, ultrasonically dispersed in deionized water, and washed by centrifugation with deionized water; (6) The washed product is completely dried to obtain a zinc-nickel composite oxide nanopowder material. The X-ray diffraction spectrum of the obtained nanopowder is as follows: Figure 5As shown in curve f, the results show that the oxide is a zinc-nickel composite oxide.
[0061] Embodiment 11
[0062] (1) 10g potassium nitrate, 5g potassium chloride, 2g nickel nitrate, 2g cobalt nitrate, 0.9g sodium hydroxide and 2.1g urea are fully mixed to form a mixed reactant; (2) In an argon atmosphere, the temperature is increased from room temperature to 500°C at a heating rate of 0.5°C / min, and the reaction is kept at this temperature for 2 hours; (3) The temperature is cooled to 120°C in the furnace and kept at this temperature for 2 hours; (4) The temperature is increased to 200°C at a heating rate of 5°C / min and the reaction is carried out for 2 hours; (5) The product of step (4) is cooled to room temperature in the furnace, ultrasonically dispersed in deionized water, and washed by centrifugation with deionized water; (6) The washed product is completely dried to obtain a nickel-cobalt composite oxide nanopowder material. The X-ray diffraction spectrum of the obtained nanopowder is as follows: Figure 6 As shown in curve g, the results show that the oxide is a nickel-cobalt composite oxide.
[0063] Example 12
[0064] (1) 10g potassium nitrate, 5g potassium chloride, 4g nickel nitrate, 2g cobalt nitrate, 0.9g sodium hydroxide and 2.1g urea are fully mixed to form a mixed reactant; (2) In an argon atmosphere, the temperature is increased from room temperature to 500°C at a heating rate of 1°C / min, and the reaction is kept at this temperature for 2 hours; (3) The temperature is cooled to 150°C in the furnace and kept at this temperature for 2 hours; (4) The temperature is increased to 200°C at a heating rate of 1°C / min and the reaction is carried out for 2 hours; (5) The product of step (4) is cooled to room temperature in the furnace, ultrasonically dispersed in deionized water, and washed by centrifugation with deionized water; (6) The washed product is completely dried to obtain a nickel-cobalt composite oxide nanopowder material. The X-ray diffraction spectrum of the obtained nanopowder is as follows: Figure 6 As shown in curve h, the results show that the oxide is a nickel-cobalt composite oxide.
[0065] Embodiment 13
[0066] (1) 10 g potassium nitrate, 5 g potassium chloride, 2 g nickel nitrate, 4 g cobalt nitrate, 0.9 g sodium hydroxide and 2.1 g urea are fully mixed to form a mixed reactant; (2) In an argon atmosphere, the temperature is increased from room temperature to 500°C at a heating rate of 10°C / min, and the reaction is kept at this temperature for 2 hours; (3) The temperature is cooled to 120°C in the furnace and kept at this temperature for 3 hours; (4) The temperature is increased to 200°C at a heating rate of 10°C / min and the reaction is carried out for 2 hours; (5) The product of step (4) is cooled to room temperature in the furnace, ultrasonically dispersed in deionized water, and washed by centrifugation with deionized water; (6) The washed product is completely dried to obtain a nickel-cobalt composite oxide nanopowder material. The X-ray diffraction spectrum of the obtained nanopowder is as follows: Figure 6As shown in curve i, the results show that the oxide is a nickel-cobalt composite oxide.
[0067] Embodiment 14
[0068] (1) 10g potassium nitrate, 5g potassium chloride, 3g nickel nitrate, 3g cobalt nitrate, 0.9g sodium hydroxide and 2.1g urea are fully mixed to form a mixed reactant; (2) In an argon atmosphere, the temperature is increased from room temperature to 500°C at a heating rate of 0.5°C / min, and the reaction is kept at this temperature for 2 hours; (3) The temperature is cooled to 80°C in the furnace and kept at this temperature for 2 hours; (4) The temperature is increased to 200°C at a heating rate of 5°C / min and the reaction is carried out for 2 hours; (5) The product of step (4) is cooled to room temperature in the furnace, ultrasonically dispersed in deionized water, and washed by centrifugation with deionized water; (6) The washed product is completely dried to obtain a nickel-cobalt composite oxide nanopowder material. The X-ray diffraction spectrum of the obtained nanopowder is as follows: Figure 6 As shown in curve j, the results show that the oxide is a nickel-cobalt composite oxide.
[0069] The X-ray diffraction patterns of the composite metal oxide nanopowders prepared in Examples 5 to 14 of the present invention are: a is the copper-iron composite oxide prepared in Example 5, b is the nickel-iron composite oxide prepared in Example 6, c is the cobalt-copper composite oxide prepared in Example 7, d is the iron-manganese composite oxide prepared in Example 8, e is the zinc-copper composite oxide prepared in Example 9, f is the zinc-nickel composite oxide prepared in Example 10, and g, h, i, and j are the nickel-cobalt composite oxides prepared in Examples 11, 12, 13, and 14, respectively. Figure 5 The curve shows that by adjusting different preparation parameters and raw materials, this technology can prepare a variety of metal oxides; Figure 6 The relative peak intensity of the diffraction peaks of the curve shows that the crystallinity and quality of the nickel-cobalt composite oxide nanopowder can be controlled by adjusting the preparation parameters. The greater the temperature difference between the reaction temperature of step (2) and step (3), the better the crystallinity of the product, and the greater the amount of the mixed reactants, the greater the quality of the product.
[0070] The material prepared by the present invention is a composite metal oxide nano powder, the raw material cost is low, it is easy to obtain, the product is widely used, has great potential in many fields, the preparation process is simple and efficient, the equipment and atmosphere requirements are low, it is easy to control, the production process does not use water as a solvent, does not cause water pollution, and is environmentally friendly. Therefore, the present invention not only provides a method for quickly preparing composite metal oxide nano powder, but also is applicable to a variety of composite metal oxides, and can also be used to explore the synthesis and acquisition of new composite metal oxides. By adjusting the type and amount of raw materials, reaction time and temperature, it is also easy to control the product phase, morphology, size, crystallinity, etc.
[0071] The embodiments and applications described above are all specific implementation methods of the technical solution of the present invention, which are further detailed descriptions of the technical solution of the present invention. However, the design concept of the present invention is not limited thereto. Any simple modification, equivalent change or improvement made thereto based on the technical essence of the present invention should still fall within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing composite metal oxide nanopowder, characterized in that: The steps include: (1) fully mixing a precursor salt, salts of two different metal sources, sodium hydroxide or potassium hydroxide, and urea in a certain mass ratio to form a mixed reactant; The sodium hydroxide or potassium hydroxide is used as a dispersant, and the degree of mutual adhesion between the nanoparticles of the composite metal oxide nanopowder material in step (6) is regulated by adjusting the amount of the dispersant: By increasing the amount of sodium hydroxide or potassium hydroxide, the degree of adhesion between nanoparticles is reduced, and powder with a smaller particle size is obtained; By reducing the amount of sodium hydroxide or potassium hydroxide, the degree of adhesion between nanoparticles is reduced, and a powder with a larger particle size is obtained; (2) In an inert gas atmosphere, the mixed reactants of step (1) are heated from room temperature to a reaction temperature at a certain heating rate, kept heated to a molten state, and reacted for a period of time; (3) cooling the reaction system of step (2) to a certain temperature along with the furnace, and keeping the temperature for a period of time; (4) heating the reaction system of step (3) to a secondary reaction temperature at a certain heating rate and reacting for a period of time; (5) cooling the product of step (4) to room temperature in the furnace, dispersing it in deionized water by ultrasonic, and washing it by centrifugation with deionized water; (6) Completely drying the washed product to obtain a composite metal oxide nanopowder material.
2. The method for preparing composite metal oxide nanopowder according to claim 1, characterized in that: The precursor salt refers to a salt with a melting point below 500° C., including any one or more of the following mixtures: nitrate, chloride, sulfate, phosphate, acetate, and carbonate.
3. The method for preparing composite metal oxide nanopowder according to claim 1, characterized in that: The salts of the two different metal sources include nitrates, sulfates, chlorides, phosphates, titanates, tungstates, acetates, molybdates or carbonates of any two of the metal elements copper, manganese, nickel, cobalt, zinc, iron, titanium, aluminum, tin, vanadium, chromium, molybdenum, ruthenium, tungsten, zirconium, lanthanum and cerium; wherein the mass ratio of the salts of the two different metal sources is in the range of 10 to 0.1:
1.
4. The method for preparing composite metal oxide nanopowder according to claim 1, characterized in that: The mass ratio of the precursor salt, the salts of two different metal sources, sodium hydroxide or potassium hydroxide, and urea is (100-1):(50-0.5):(5-1):
1.
5. The method for preparing the composite metal oxide nanopowder according to any one of claims 1 to 4, characterized in that: The heating rate in step (4) is in the range of 0.5 to 10° C. / min, the reaction temperature is in the range of the melting point to the decomposition temperature of the precursor salt, and the reaction time is in the range of 60 seconds to 6 hours.
6. The method for preparing composite metal oxide nanopowder according to claim 5, characterized in that: The heating rate in step (2) is in the range of 0.5 to 10° C. / min, the reaction temperature is in the range of the melting point to the decomposition temperature or boiling point of the precursor salt, and the reaction time is in the range of 60 seconds to 6 hours.
7. The method for preparing composite metal oxide nanopowder according to claim 5, characterized in that: The temperature range of cooling to a certain temperature in the step (3) is 50 to 150° C., and the range of the heat preservation time is 0.5 to 5 hours.
8. The method for preparing composite metal oxide nanopowder according to claim 5, characterized in that: The size and morphology of the nanoparticles of the composite metal oxide nanopowder material in step (6) are adjusted by adjusting the heating rates in step (2) and step (4): By increasing the heating rate, the size of the nanoparticles increases and the nanoparticles form a polyhedral structure; by decreasing the heating rate, the size of the nanoparticles decreases and the nanoparticles form a spherical structure.
9. The method for preparing composite metal oxide nanopowder according to claim 5, characterized in that: The degree of crystallization of the composite metal oxide nanopowder material is regulated by regulating the reaction temperature in step (2) and the certain temperature in step (3): By increasing the temperature difference between the reaction temperature in step (2) and the certain temperature in step (3), the degree of crystallization is increased, and by decreasing the temperature difference between the reaction temperature in step (2) and the certain temperature in step (3), the degree of crystallization is decreased.
Citation Information
Patent Citations
A method for preparing ion-intercalated two-dimensional materials
CN106629613B
A method for preparing manganese-chromium binary metal oxide energy storage materials and their applications
CN108242539B
Preparation methods of metal oxides or their composites, applications of metal oxides or their composites, and batteries.
CN109437341B
Multi-element metal oxide nanosheet and preparation method thereof
CN117865232A
Iron-silicon magnetic powder core coated with bimetal oxide in situ and preparation method of iron-silicon magnetic powder core
CN118486520A